2017
DOI: 10.1159/000475661
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Evaluation of Brain Stem Atrophy Using Magnetic Resonance Imaging in Adult Patients with Alexander Disease

Abstract: Brain MRI in adult patients with Alexander disease (AxD) mainly shows atrophy in the medulla oblongata. However, currently there is no quantitative standard for assessing this atrophy. In this study, we quantitatively evaluated the brain stem of AxD patients with glial fibrillary acidic protein (GFAP) mutation using conventional MRI to evaluate its usefulness as an aid to diagnosing AxD in daily clinical practice. Nineteen AxD patients with GFAP mutation were compared with 14 patients negative for GFAP mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“… a These patients had been diagnosed with the bulbospinal type 8 , but they were subsequently classified with the intermediate form based on strict re-evaluation in this study.Ref = reference; F = female; M = male; NA = not available. Phenotypic differences in patients with the same genotype may be due to genetic modifiers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a These patients had been diagnosed with the bulbospinal type 8 , but they were subsequently classified with the intermediate form based on strict re-evaluation in this study.Ref = reference; F = female; M = male; NA = not available. Phenotypic differences in patients with the same genotype may be due to genetic modifiers.…”
Section: Resultsmentioning
confidence: 99%
“…a These patients had been diagnosed with the bulbospinal type 8 , but they were subsequently classified with the intermediate form based on strict re-evaluation in this study.…”
Section: Resultsmentioning
confidence: 99%
“…He was unable to walk in tandem gait, and had nystagmus, diplopia and slight dysarthria. Atrophy, from the medulla oblongata to the superior cervical cord, is a well-known feature of AOAD in MRI, and the sagittal diameter of the medulla oblongata (< 9.0 mm) is useful for the diagnosis of the disease with high sensitivity and specificity 3,4 .…”
Section: Case Reportmentioning
confidence: 99%
“…It was rather swollen in the early stages of the disease. We compared the sagittal diameter of the medulla oblongata in this case with the diameter of the cases in the control group included in a study reported by Yoshida et al 4 . The medullary diameter of the control group was 12.3 ±1.5 mm (mean ±SD), and the Z-scores at each age (45, 50, 55, and 58 years) in this case were 3.13,…”
Section: Case Reportmentioning
confidence: 99%
“…B, C: a 3-month-old early-onset ALXDRD patient. 46) . In elderly patients or mild cases, abnormal signals of the pyramid of the MO, which are like "eye spots" of butterflies, can be shown (B) 45) .…”
mentioning
confidence: 99%